Faktor-faktor yang Berhubungan dengan Keluhan Nyeri Punggung Bawah Supir Bus DAMRI - Syafa Istiqomah; Widi Raharjo; Agus Fitriangga (PT Kalbe Farma Tbk., 2024)
Background: Low back pain (LBP) is a musculoskeletal disorder in the lower back region caused by various diseases and activities. LBP among drivers can be caused by individual factors, demographic factors, vehicle design, occupational, and environmental factors. This study aims to determine factors related to low back pain in DAMRI Pontianak-Pangkalan Bun route bus drivers. Method: Observational analytical research with cross-sectional method. Respondents were 30 drivers. Independent variables were age, years of service, driving duration, exercise habits, and body mass index (BMI), while the dependent variable was low back pain. Result: Low back pain was found in 73,3% of respondents, 70% were 35 years old or older, 80% had 5 years of service or more, 50% had 8 hours of driving duration, 60% had poor exercise habits, and 40% were overweight. The chi-square test resulted in significance for age, years of service, driving duration, and exercise habits (p<0.05). Conclusion: Age, years of service, driving duration, and exercise habits were related to low back pain among DAMRI Pontianak-Pangkalan Bun route bus drivers.